AL-QUR’AN DAN RITUS BUDAYA (Analisis Living Qur’an Dalam Peringatan Nuzulul Qur’an Di Tengah Masyarakat Indonesia) - Maulana, Daafiqin Syaqiq (Institut Dirosat Islamiyah Al-Amien Prenduan, 2025)
The purpose of Nuzulul Qur'an event among Indonesian people is to introduce the basic things of Nuzululul Qur'an, but unfortunately not all oral messages delivered are the basic things of Nuzulul Qur'an but the cultural value of Nuzulul Qur'an event. Therefore, this study analyzes the basic points of Nuzulul Qur'an and the generalization of the community about the Nuzulul Qur'an event. The research paradigm used is the literature method and open-ended questionnaires. The conclusion regarding the basic points can be divided into four parts, while the generalization of the cultural value of the Nuzulul Qur'an event shows positive things that motivate Muslims to do good things.